Evaluasi penerapan Pernyataan Standar Akuntansi Pemerintah (PSAP) Nomor 02 tentang Laporan Realisasi Anggaran (Studi kasus pada Kantor Dinas Kepemudaan dan Olahraga Kota Tomohon) - Rindengan, Anatasia Maria Trisilia; Kapojos, Peter M. (Riset Akuntansi dan Portofolio Investasi, 2024)
The Budget Realization Report (LRA) is a report that presents information on the realization of income, expenditure, transfers, surplus/deficit, financing, and remaining more/less budget financing, each of which is compared with the budget in one period. In its implementation, budget realization reports always refer to applicable regulations and use applications that have been prepared and proven by documents and even accountability reports.. This study aims to find out and evaluate the application of Government Accounting Standards Statement No. 02 regarding whether or not the presentation of the budget realization report prepared by the Tomohon City Youth and Sports Service Office is in accordance with Government Regulation no. 71 of 2010 concerning Government Accounting Standards. The results of the study show that implementattion of the budget realization report (LRA) at the Tomohon City Youth and Sports Service office is in in accordance with the statement of Government Accounting Standards (PSAP) No.02 in Government Regulation Number 71 of 2010, this can be seen from the results of the comparison between the application of The Budget Realization Report ( LRA) implemented by the Tomohon City Youth and Sports Department and the implementation of The Budget Realization Report (LRA) based on the Government Accounting Standards (PSAP) statement No. 02 in Government Regulation Number 71 of 2010.